1995
DOI: 10.1001/archneur.1995.00540350048016
|View full text |Cite
|
Sign up to set email alerts
|

The Value of PET Scan (and MRI and Wada Test) in Patients With Bitemporal Epileptiform Abnormalities

Abstract: In this highly selected group of patients, the lateralizing value of PET and magnetic resonance imaging was somewhat diminished, and the intracarotid amobarbital procedure was not found useful for lateralization. Positron emission tomography and magnetic resonance imaging, when pointing to the side opposite depth EEG, may indicate a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 28 publications
1
27
1
2
Order By: Relevance
“…The degree of lateralization is defined as the number of IEDs originating from one hemisphere as compared with the total number of IEDs originating from both hemispheres. Epileptiform activity has often been considered "lateralized" in TLE by many investigators if >80-90% of the discharges originated from one temporal lobe (4,6,10,17,19). Our study showed that 13 (76%) of 17 patients with bilateral independent IEDs (see Table 1) would be considered not to have lateralized discharges by using the 90% criterion, although all the patients had only unilateral IEDs in routine short-term EEGs.…”
Section: Discussionmentioning
confidence: 65%
“…The degree of lateralization is defined as the number of IEDs originating from one hemisphere as compared with the total number of IEDs originating from both hemispheres. Epileptiform activity has often been considered "lateralized" in TLE by many investigators if >80-90% of the discharges originated from one temporal lobe (4,6,10,17,19). Our study showed that 13 (76%) of 17 patients with bilateral independent IEDs (see Table 1) would be considered not to have lateralized discharges by using the 90% criterion, although all the patients had only unilateral IEDs in routine short-term EEGs.…”
Section: Discussionmentioning
confidence: 65%
“…Some of Group I patients might prove not to have TLE despite clinical and neurophysiological clues suggestive of a temporal lobe onset. Earlier series dealing with heterogeneous populations have not emphasized imaging findings [15][16][17][18] . The majority of Group I patients had no demonstrable pathology within the surgical specimen.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Hypometabolism in the extratemporal cortex (including the temporal cortex contralateral to the seizure focus) on FDG PET is not an uncommon finding in TLE [3,5,6,7]. Extratemporal hypometabolism seems to be associated with a poor seizure outcome after surgery in TLE [3,5,6,7].…”
Section: Introductionmentioning
confidence: 99%